2015
DOI: 10.1523/jneurosci.4668-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Deprivation and Immune Suppression in a Mouse Model of Alzheimer's Disease

Abstract: The pathogenesis of Alzheimer's disease (AD) is a critical unsolved question; and although recent studies have demonstrated a strong association between altered brain immune responses and disease progression, the mechanistic cause of neuronal dysfunction and death is unknown. We have previously described the unique CVN-AD mouse model of AD, in which immune-mediated nitric oxide is lowered to mimic human levels, resulting in a mouse model that demonstrates the cardinal features of AD, including amyloid depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 114 publications
8
141
3
Order By: Relevance
“…In addition, we provided evidence that in human AD brain, CASP4 significantly correlates with expression of IL1B and IL6, while correlation with ARG1 or CHIT1 are moderate or low. Although we found no correlation with iNOS expression, this was not altogether surprising as it has been well documented that human iNOS expression is clearly distinct from the mouse counterpart (63)(64)(65). A previous study showed that infiltrating macrophages recruited to amyloid plaques increased expression of proinflammatory cytokines including IL-1b (23).…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, we provided evidence that in human AD brain, CASP4 significantly correlates with expression of IL1B and IL6, while correlation with ARG1 or CHIT1 are moderate or low. Although we found no correlation with iNOS expression, this was not altogether surprising as it has been well documented that human iNOS expression is clearly distinct from the mouse counterpart (63)(64)(65). A previous study showed that infiltrating macrophages recruited to amyloid plaques increased expression of proinflammatory cytokines including IL-1b (23).…”
Section: Discussioncontrasting
confidence: 59%
“…[105][106][107][108] More recently, a new potential cause for AD has been found in the behavior of certain immune cells that normally protect the brain instead beginning to consume a vital nutrient: the amino acid arginine. 109 This new discovery has implications not only in a new potential cause of the disease but also as a new strategy for targeting disease.…”
Section: Data Extractionmentioning
confidence: 99%
“…An increasing number of studies have reported changes in immune system activity, namely, alterations in lymphocyte and macrophage distribution and activation, production of antibodies against self-proteins, as well as atypical proinflammatory factors [25][26][27]. A recent study showed that the pathogenesis of AD in APPSwDI(+)/(+)mNos2(−/−)(CVN)-AD mice is driven by local immune suppression as areas of hippocampal neuronal death are associated with the presence of immunosuppressive CD11c + microglia and extracellular arginase, resulting in arginine catabolism and reduced levels of total brain arginine [28]. In this study, pharmacologic disruption of the arginine utilization pathway significantly decreased the expression of CD11c and protected from AD-like pathology [28].…”
Section: Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%
“…A recent study showed that the pathogenesis of AD in APPSwDI(+)/(+)mNos2(−/−)(CVN)-AD mice is driven by local immune suppression as areas of hippocampal neuronal death are associated with the presence of immunosuppressive CD11c + microglia and extracellular arginase, resulting in arginine catabolism and reduced levels of total brain arginine [28]. In this study, pharmacologic disruption of the arginine utilization pathway significantly decreased the expression of CD11c and protected from AD-like pathology [28]. These results raise the question of whether CNS resident microglia or their myeloid counterparts that cross the BBB [24] are beneficial or have deleterious effects and when would be the best time to intervene in microglia activity during disease development and progression.…”
Section: Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%